Three-factor assessment of rutting factor of modified asphalt binders and mastics in the ageing process - Mielczarek, Marta; Andrzejczak, Karol; Słowik, Mieczysław (Bulletin of the Polish Academy of Sciences Technical Sciences, 2025)
This paper discusses the research and multivariate analyses of the rheological properties of asphalt binders and mastics containing arious mineral fillers and SBS copolymer-modified bitumen. In the experimental design employed, three types of mineral filler were used: limestone, basalt, or granodiorite. To determine the effect of ageing processes on the rheological properties of the obtained mastics, all asphalt binders tested were subjected to short-term (technological) ageing simulated under laboratory conditions using the RTFOT method. The main aim of this study was to evaluate the rutting resistance of modified binders and asphalt mastics depending on such factors as: the type of mineral filler, the percentage of SBS copolymer, temperature, and the influence of the ageing process. A three-way ANOVA was used to test for rutting resistance. The results of laboratory tests and statistical analyses made it possible to assess the significance of the factors examined in the research on the rutting resistance of asphalt binders and mastics, both before and after short-term ageing.